Advanced coal preparation and beyond : CO capture conversion of waste to byproducts - Kawatra, S. K. (Boca Raton, FL : CRC Press/Taylor & Francis, 2020)
"Updating content from the author's 2001 book Coal Desulfurization, this new title focuses on CO sequestration and utilization. It includes information on the theory and practical approaches to CO capture and recent advances in the use of sequestered CO"--
3.2.1.4 Dry Sorbent Injection -- 3.2.1.5 SNOX System -- 3.2.2 In-Combustor Technologies -- 3.2.2.1 Fluid-Bed Combustion (FBC) -- 3.2.2.2 Integrated Gasification Combined Cycle -- 3.3 Relative Costs of Sulfur Control Processes -- 3.3.1 Postcombustion Sulfur Removal Costs -- 3.3.2 Benefits of Combining Precombustion and Postcombustion Desulfurization -- 3.4 Summary -- References -- Chapter 4 Heavy-Media Separation -- 4.1 Determination of Sulfur-Removal Ability of Density Separators -- 4.2 Case Study: Analysis of Sulfur Removal at the Meigs Plant -- 4.2.1 Plant Description
OCLC-licensed vendor bibliographic record.
Keywords: Clean coal technologies; Carbon sequestration; Coal -- Combustion -- By-products.; TECHNOLOGY / Engineering / Chemical & Biochemical